Letter - Stockton and Thornaby Trades & Labour Council, 9 May 1926 (page 2)
1926-05-09 "Letter - Stockton and Thornaby Trades & Labour Council, 9 May 1926 (page 2)" [g0133002.jpg], 9 May 1926, Stockton and Thornaby Trades & Labour Council